Students Subject-Verb Agreement Errors in Paragraph Writing Class - Mali, Yustinus Calvin Gai; Yulia, Made Frida (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
Subject-verb agreement is an essential element to master by English Language Education Study Program (ELESP) students, who are prepared to be English teachersin the future. However, the researchers still find the fact that ELESP students makethe errors on the agreement. For that reason, it would be significant to find out theerrors made by the students as well as to discover the factors behind the errors.To achieve those purposes, the researchers conducted a document analysis and asemi-structure interview.The research results showed most of the errors belongedto misinformation category (71.4%) and were subsequently followed by omissioncategory (17.9%) and addition category (10.7%). In addition, from the interview,the researchers also found five (5) major factors that caused the students to makethe errors, namely interlingual error, ignorance of rule restrictions, incompleteapplication of rules, false concepts hypothesized, and carelessness.